17-2x=-5x+17

Simple and best practice solution for 17-2x=-5x+17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17-2x=-5x+17 equation:



17-2x=-5x+17
We move all terms to the left:
17-2x-(-5x+17)=0
We get rid of parentheses
-2x+5x-17+17=0
We add all the numbers together, and all the variables
3x=0
x=0/3
x=0

See similar equations:

| 2(4x+11)=10 | | 9-(n)/4=15 | | 3(x-4)=-2(x-16) | | 60+42.25x=25+49.95 | | -2(18-3y=7y+2y | | 45=3b+6 | | 3(6x-8)=6(3x-6) | | s+(-2/3)=3/5 | | x/2+7=17 | | 9x+5-7x=3x-9+x | | 2/3=18/5+x | | (x*2-x-2)(9x+36)=0 | | w^2+17w+70=0 | | 2x+80=7x | | 15a-2(4a+5)=(-6a) | | 74=14=5m | | 19+4n=-10 | | Y=-4/9x+3 | | 3+4x-5x=-10 | | x+4=2x-8((1/4)x)-(1/4) | | 7x=2x−35 | | 75=5-7x | | 2+5(4k+2)=12k | | -4(2x-5)=92 | | W=15h+7 | | (x-5)x2=10 | | m/9=5=12 | | 4(2a+3)=-3a+34 | | -33-3k=-6(k+4) | | 5(1+2m)=1/8(8m+20) | | 1/3h-4(2/3h-3)=2/5h-6 | | 3x-4=2(6+7x) |

Equations solver categories